What are the risk factors for admission to the pediatric intensive unit among pediatric patients with COVID-19? - Susanna Esposito; Fabio Caramelli; Nicola Principi (BMC, 2021)
Abstract Background Although with exceptions, evidence seems to indicate that children have lower susceptibility than adults to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. When infected, children generally remain asymptomatic or develop mild disease. A small number of pediatric cases required admission to the pediatric intensive care unit (PICU), respiratory support with a mechanical ventilation and additional life-saving interventions. Even if rarely, death can occur. Aim of this manuscript is to highlight the risk factors associated with severe outcome among pediatric patients with COVID-19. Main findings Early identification of SARS-CoV-2-infected children at risk of developing severe COVID-19 is vital for service planning, as severely affected pediatric patients require high-quality care and should be followed only where an adequately structured PICU is available. However, early identification of children who must be carefully monitored for substantial risk of severe COVID-19 remains difficult. An underlying comorbidity and heart involvement are frequently observed in severe paediatric cases. Reduced left ventricular systolic function with an ejection fraction < 60%; diastolic dysfunction; and arrhythmias, including ST segment changes, QTc prolongation, and premature atrial or ventricular beat, are the earliest manifestations of heart involvement. Inclusion of heart enzyme serum levels and evaluation of ventricular function among predictive markers could lead to a more effective evaluation of children at risk with proper selection of those to admit to the PICU and with more adequate treatment in case of more severe clinical manifestations. Conclusions To appropriately manage severe pediatric COVID-19 cases, greater attention should be paid to risk factors in children and adolescents, especially to cardiovascular alterations (e.g., heart enzyme serum levels and evaluation of ventricular function). Further studies are needed and the development of a validated score based on all the most common presumed markers of disease severity seems essential.